GESTÃO DA SEGURANÇA DO TRABALHO EM CONSTRUÇÃO E MONTAGEM NA INDÚSTRIA PETROQUÍMICA UM ESTUDO DE CASO - Giffoni, Daniel Araújo (2007)
This work had the objective of to present a case study about work safety management in a company that manages constructions. The practices adopted in their management were discussed and suggestions were made to improve its performance. A bibliographic research was evaluated to present the main concepts that based this work, especially: work safety and accidents, safety in construction industry, safety culture, management system and, qualitative research. It was concluded that the majority of the practices adopted by the studied company are adequate to work safety management applied to constructions, and these can be used for other companies that want to implement controls over work safety